'The Impulse to Help': (Post) humanitarianism in an era of the 'new' development advocacy. (20th May 2013) - Bryan, Audrey
This paper draws on the Republic of Ireland as a case study of the 'new' development advocacy, i.e. government, philanthropic, and celebrity humanitarian engagement with international development and statutory efforts to deepen understanding of international development among citizens in the global North (Biccum, 2010; 2011). It outlines some of the culturally specific narratives that inform the 'new' development advocacy in an Irish context, with reference to a set of recurrent tropes that have come to dominate both official and popular discourses of development 'at home'. Utilizing critical discourse analytic techniques, it illuminates the self-constituting function these public pedagogical efforts perform and highlights the function that remembering instances of historical trauma and suffering, and of forgetting or ignoring Ireland's role in the history of imperialism, play in shaping and constituting the nation through orthodox development discourses. Rooted in a critical development education framework informed by postcolonial theory (Andreotti, 2006), the paper stresses the need for alternative development discourses that open up – rather than close down – possibilities for a deeper engagement with difficult questions of individual and collective responsibility, and with what it means to 'take action' in response to global problems or to engage with the suffering of Others.